Aerodynamic, infrared extinction and tribocharing properties of nanostructured and conventional particles - Pjesky, Susana Castro (Kansas State University, 2008)
Nanostructured particles possess unique chemical and physical properties, making them excellent candidates for air purification, smoke clearing, and obscuration. This research was conducted to investigate the aerodynamic, charging, and infrared (IR) extinction properties of nanostructured particles. Specific objectives were to: (1) measure the size distribution and concentration of aerosolized nanostructured particles; (2) evaluate their IR extinction properties; (3) determine their relative chargeability; and (4) numerically model their transport in enclosed rooms. The size distribution and concentration of two nanostructured particles (NanoActive® MgO and MgO plus) were measured in an enclosed room. The particles differed in size distribution and concentration; for example, the geometric mean diameters of NanoActive® MgO and MgO plus were 3.12 and 11.1 [Mu]m, respectively. The potential of nanostructured particles as IR obscurants was determined and compared with other particles. Four groups of particles were considered: nanostructured particles (NanoActive® MgO plus, MgO, TiO[subscript2]); nanorods (MgO, TiO[subscript2]); conventional particles (NaHCO[subscript3] and ISO fine test dust); and common obscurants (brass, graphite, carbon black). The extinction coefficients of the nanostructured particles were generally significantly smaller than those of the other particles. Graphite flakes had the greatest mass extinction coefficient (3.22 m[superscript2]/g), followed by carbon black (1.72 m[superscript2]/g), and brass flakes (1.57 m[superscript2]/g). Brass flakes had the greatest volume extinction coefficient (1.64 m[superscript2]/cc), followed by NaHCO[subscript3] (0.93 m[superscript2]/cc), and ISO fine test dust (0.91 m[superscript2]/cc). The relative chargeability of nanostructured particles was also investigated. Selected particles were passed through a Teflon tribocharger and their net charge-to-mass ratios were measured. Tribocharging was able to charge the particles; however, the resulting charge was generally small. NanoActive® TiO[subscript2] gained the highest net charge-to-mass ratio (1.21 mC/kg) followed by NanoActive® MgO (0.81 mC/kg) and ISO fine test dust (0.66 mC/kg). The transport of NanoActive® MgO plus and hollow glass spheres in an enclosed room was simulated by implementing the discrete phase model of FLUENT. In terms of mass concentrations, there was reasonable agreement between predicted and measured values for hollow glass spheres but not for NanoActive® MgO plus. In terms of number concentration, there was large discrepancy between predicted and measured values for both particles.
Keywords: Nanostructured particles; Particle size distribution; Infrared extinction coefficient; Infrared obscurant; Tribocharging; Particle transport; Aerodynamic properties; Engineering, Agricultural (0539); Engineering, Environmental (0775); Environmental Sciences (0768)